Sleep Deprivation-Induced Hyperalgesia in Rodents: Some Neurochemical Mechanisms - Ibironke; G. F. Ajonijebu C. O. Ibironke (Нейрофизиология, 2014)
We assessed the effect of sleep deprivation on the pain thresholds in the thermal and chemical nociceptive tests. Adult male Wistar rats and mice were randomly assigned to the three groups, with no sleep deprivation (control), subjected to 24-h-long sleep deprivation, and sleep-deprived and treated with either an H2 (histamine) receptor antagonist, cimetidine, or a cholinergic receptor blocker, atropine, before deprivation.Sleep deprivation led to significant decreases in both hot plate and tail withdrawal latencies in the thermal tests, a significant increase in the number of writhings in the acetic acid-induced writhing test, and significant prolongation of the licking time in the formalin test (P < 0.05 in all cases). All changes in the thermal and chemical tests denote noticeable hyperalgesia. Prior administration of both cimetidine and atropine significantly reversed these hyperalgesic changes caused by sleep deprivation as revealed by increases in the thermal latencies in both tests used. We, therefore, conclude that both histaminergic and cholinergic systems play significant roles in sleep deprivation-induced hyperalgesia